Significance of gene therapy in neurodegenerative diseases - Wang, Lingling; Ma, Lin; Gao, Zihan; Wang, Ying; Qiu, Jiaoxue (Frontiers in Neuroscience, 2025)
Gene therapy is an approach that employs vectors to deliver genetic material to target cells, aiming to correct genes with pathogenic mutations and modulate one or more genes responsible for disease progression. It holds significant value for clinical applications and offers broad market potential due to the large patient population affected by various conditions. For instance, in 2023, the Food and Drug Administration (FDA) approved 55 new drugs, including five specifically for gene therapy targeting hematologic and rare diseases. Recently, with advancements in understanding the pathogenesis and development of neurodegenerative diseases (NDDs), gene therapy has emerged as a promising avenue for treating Alzheimer's disease (AD), Parkinson's disease (PD), Huntington's disease (HD), amyotrophic lateral sclerosis (ALS), and spinal muscular atrophy (SMA), particularly in personalized medicine. Notably, the FDA has approved three clinical applications for combating SMA, utilizing viral vectors delivered via intravenous and intrathecal injections. However, gene therapy for other NDDs remains in clinical trials, necessitating improvements in viral vectors, exploration of new vectors, optimization of delivery routes, and further investigation into pathogenesis to identify novel targets. This review discusses recent advancements in gene therapy for NDDs, offering insights into developing new therapeutic strategies.